Re-casting Terra Nullius Blindness : Empowering Indigenous Protocols and Knowledges in Australian University Built Environment Education : Final Report. - Jones, David; Choy, Darryl Low; Revell, Grant; Heyes, Scott; Tucker, Richard; Bird, Susan (Dept of Education and Training Australia, 2017)
Recent events in Australian history, including recognition of native title by the High Court in Mabo v the State of Queensland [No. 2] (1992) 175 CLR 1, have heightened recognition of the rights, interests, needs and aspirations of Aboriginal and Torres Strait Islander people in Australia and internationally. Despite this, little has changed in Australian built environment professional education to integrate a better understanding of the need for engagement with Indigenous knowledge and cultural systems and relevant protocols, as distinct from cultural competency articulation. While aspirations of including a better understanding of Indigenous Australian's knowledge and cultural systems are embodied in the relevant agendas of the respective discipline professional Institutes, little attempt has been made to realize this objective. This is the final report from a project that sought to re-dress this deficiency by providing Australian universities with tools to address practice realities and complexities through a nationally applicable cross-discipline educational module that to aid Indigenous and non-Indigenous cultural literacy in this context.